Analisis Rasio Keuangan terhadap Harga Saham pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia - Nurjanti Takarini; Octavia Dara Citra Dewi (Universitas Batanghari Jambi, 2023)
This study was conducted with the aim of knowing the effect of financial ratios namely Return on Assets, Current Ratio and Earning Per Share on stock prices in the pharmaceutical industry listed on the Indonesia Stock Exchange. The data used by researchers is in the form of secondary data, namely using recorded financial reports and published on the Indonesian Stock Exchange for the period 2018 - 2021. There are 14 companies that are included in the research sample criteria. The tools for the analysis used are multiple regression with the F test, t test and the coefficient of determination with the classical assumption test and processed using the SPSS data processing program. The gains from this study show simultaneously that all variables have a positive and significant effect on stock prices. With the acquisition of adjusted R-square (R2) of 0.365, it shows that the variables from ROA, CR and EPS have an influence on stock prices of 36.5% with a residual value of 63.5% with the influence of variables outside the research.